Próba zastosowania modeli ścieżkowych do analizy głębokości ubóstwa - Szwarc, Krzysztof (Attempt to Using Path Analysis to Researching on Poverty Gap, 2005)
Path analysis is the method of measure of influences between variables. It permits to define factors which determine a low earnings, so variables which determine poverty gap too. The research was done on poor households, which lived in Jeżyce district in Poznań. Between factors determining earnings are among other things: age, sex, health and education of head of household and also place of living, number of people in household, number of working people in household. By means of path analysis I measured influence of some variables on earnings this household.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 311-318